HUBUNGAN MOBILISASI DINI DENGAN PROSES INVOLUSIO PADA IBU POST PARTUM DI RSKD IBU DAN ANAK SITI FATIMAH MAKASSAR - Maria Sonda; Anastasya Ponny Marampa; Ros Rahmawati; Subriah Subriah; Marhaeni Marhaeni (Jurnal Midwifery, 2022)
Introduction Early Mobilization is the movement that is done as early as possible by training the body parts to stretch or learn to walk. Early mobilization can be done 2 hours after the mother gives birth by learning to tilt left and right. the mother learns to sit in bed, the mother learns to stand next to the bed and follow the walking. This study aims to determine the relationship of Early Mobilization with Involutiono process in post partum mother in RSKD mother and child Siti Fatimah Makassar. Method This research use analytic survey with research design is cross sectional study. research conducted in february-april 2018, with a sample of 55 respondents were taken using the formula lameshow. data collected by using observation sheet. data processing is done by computerized with SPSS. data analysis with chi-squre statistical test. Result of 55 respondents who did early mobilization with 38 people experienced Involutiono process with normal. based on statistical test using chi-square in get that there is 1 cell which have value expected less than 5, it does not fulfill requirement of chi-square usage. therefore researchers use fisher's exact test test that shows probability value (0,000) <a value 0.05 (0.000 <0.05), then H1 is received and Ho is rejected. Conclusion That there is an early mobilization relationship with involutiono process in post partum mother. expected in health service institutions, in order to implement early mobilization in postpartum at least 2 hours after delivery because it is very good for the process of involutiono running normally.